A novel recombinant anti‐epidermal growth factor receptor peptide vaccine capable of active immunization and reduction of tumor volume in a mouse model. (16th November 2017) - Asadi‐Ghalehni, Majid; Rasaee, Mohamad Javad; RajabiBazl, Masoumeh; Khosravani, Masood; Motaghinejad, Majid; Javanmardi, Masoud; Khalili, Saeed; Modjtahedi, Helmout; Sadroddiny, Esmaeil
ABSTRACT: Over‐expression of epidermal growth factor receptor (EGFR) has been reported in a number of human malignancies. Strong expression of this receptor has been associated with poor survival in many such patients. Active immunizations that elicit antibodies of the desired type could be an appealing alternative to conventional passive immunization. In this regard, a novel recombinant peptide vaccine capable of prophylactic and therapeutic effects was constructed. A novel fusion recombinant peptide base vaccine consisting of L2 domain of murine extra‐cellular domain–EGFR and EGFR mimotope (EM‐L2) was constructed and its prophylactic and therapeutic effects in a Lewis lung carcinoma mouse (C57/BL6) model evaluated. Constructed recombinant peptide vaccine is capable of reacting with anti‐EGFR antibodies. Immunization of mice with EM‐L2 peptide resulted in antibody production against EM‐L2. The constructed recombinant peptide vaccine reduced tumor growth and increased the survival rate. Designing effective peptide vaccines could be an encouraging strategy in contemporary cancer immunotherapy. Investigating the efficacy of such cancer immunotherapy approaches may open exciting possibilities concerning hyperimmunization, leading to more promising effects on tumor regression and proliferation.